2009
DOI: 10.2987/08-5815.1
|View full text |Cite
|
Sign up to set email alerts
|

Response of Adult Mosquitoes to Light-emitting Diodes Placed in Resting Boxes and in the Field

Abstract: The response of adult mosquitoes to 4 light-emitting diode (LED) wavelengths was evaluated using diode-equipped sticky cards (DESCs) and diode-equipped resting boxes at 2 sites in north central Florida. Wavelengths evaluated were blue (470 nm), green (502 nm), red (660 nm), and infrared (IR) (860 nm). When trapping with DESCs, 15 mosquito species from 7 genera (Aedes, Anopheles, Coquillettidia, Culex, Mansonia, Psorophora, and Uranotaenia) were captured. Overall, approximately 43.8% of all mosquitoes were trap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 12 publications
0
27
0
Order By: Relevance
“…), similar to blood‐feeding mosquitoes (Bentley et al. ), frog‐biting midges do not show this behavior and in fact respond by decreasing their movements in response to light (McMahon et al. unpub.…”
Section: Discussionmentioning
confidence: 97%
“…), similar to blood‐feeding mosquitoes (Bentley et al. ), frog‐biting midges do not show this behavior and in fact respond by decreasing their movements in response to light (McMahon et al. unpub.…”
Section: Discussionmentioning
confidence: 97%
“…gambiae s.l. as well as males are obtained by collection of resting mosquitoes [39,40]. This accounts for the use of resting boxes, pyrethrum spray catches, clay pots and manual aspiration of resting mosquitoes especially in studies associated with the estimation of the entomological inoculation rate [36,41].…”
Section: Discussionmentioning
confidence: 99%
“…Within-family or within-genus variations in light attraction are common. For instance, mosquitoes can exhibit attraction to blue or UV lights depending on the species (Bentley et al, 2009). Based on the results of the present bioassay arena study, C. sonorensis may be using UV light as a visual cue, which is often related to sugar seeking or escaping.…”
Section: Discussionmentioning
confidence: 99%
“…Other insect behavioural studies have observed insect attraction only to broader bands (∼ 50 nm) of light colours. For example, tsetse flies (Diptera: Glossinidae) are most attracted to blue light (Steverding & Troscianko, ), whereas certain genera or species of mosquito are more attracted to green and UV light (Burkett et al ., ; Bentley et al ., ), and Culicoides prefer green and UV light (Bishop et al ., ). Nocturnally active insects are generally attracted to light of differing contrast and intensity (Allan et al ., ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation